Regional metamorphism at extreme conditions: Implications for orogeny at convergent plate margins - Zheng, Yong-Fei; Chen, Ren-Xu (Journal of Asian earth sciences, 2017)
[Display omitted] •Alpine-type HP to UHP metamorphism is associated with crustal subduction at low geothermal gradients.•Barrovian/Buchan-type HT to UHT metamorphism is associated lithospheric thinning at high geothermal gradients.•Metamorphic dehydration of crustal rocks is dominant in cold to ultracold subduction zones.•Hydration and dehydration melting of metamorphic rocks is significant in hot to ultrahot orogens.•Active continental rifting develops subsequent to thinning of subduction-thickened lithosphere. Regional metamorphism at extreme conditions refers either to Alpine-type metamorphism at low geothermal gradients of <10°C/km, or to Buchan-type metamorphism at high geothermal gradients of >30°C/km. Extreme pressures refer to those above the polymorphic transition of quartz to coesite, so that ultrahigh-pressure (UHP) eclogite-facies metamorphism occurs at mantle depths of >80km. Extreme temperatures refer to those higher than 900°C at crustal depths of ≤80km, so that ultrahigh-temperature (UHT) granulite-facies metamorphism occurs at medium to high pressures. While crustal subduction at the low geothermal gradients results in blueschist-eclogite facies series without arc volcanism, heating of the thinned orogenic lithosphere brings about the high geothermal gradients for amphibolite-granulite facies series with abundant magmatism. Therefore, UHP metamorphic rocks result from cold lithospheric subduction to the mantle depths, whereas UHT metamorphic rocks are produced by hot underplating of the asthenospheric mantle at the crustal depths. Active continental rifting is developed on the thinned lithosphere in response to asthenospheric upwelling, and this tectonism is suggested as a feasible mechanism for regional granulite-facies metamorphism, with the maximum temperature depending on the extent to which the mantle lithosphere is thinned prior to the rifting. While lithospheric compression is associated with subduction metamorphism in accretionary and collisional orogens, the thinned orogenic lithosphere undergoes extension due to the asthenospheric upwelling to result in orogen-parallel rifting metamorphism and magmatism. Thus, the rifting metamorphism provides a complement to the subduction metamorphism and its operation marks the asthenospheric heating of the orogenic lithosphere. Because of the partial melting and melt extraction of the lower continental crust, contemporaneous granite-migmatite-granulite associations may serve as a petrological indicator of rifting orogeny that is superimposed on precedingly accretionary and collisional orogens. The UHT metamorphic rocks have occurred since the Archean, suggesting that the hot underplating has operated very early in the Earth’s history. In contrast, the UHP metamorphic rocks primarily occur in the Phanerozoic, indicating that the thermal regime of many subduction zones has changed since the Neoproterozoic for the cold subduction.